Development of Degraded Forests and Industry and the Proposed Forest Act - Banerjee, U. K. (Indian Forester, 1996)
The proposed Conservation of Forest and Natural Ecosystem Act proposes to involve woodbased industries to raise their raw materials by donating government degraded forest lands through State Forest Corporations. But the silver lining in the dark clouds of deteriorating forest cover of India are far too drawn. Objections to the proposed shift has been discussed.